Refund of Funds in Default Agreements in Regional/City Government Projects DSN-MUI Fatwa Perspective No.43/DSN-MUI/VIII/2004 - Siregar, Dea Ratna Sari; Marlina Tarigan, Tetty (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
City/regional governments have several plans to develop public facilities and infrastructure for the benefit of the community. The development of facilities and infrastructure is one of the programs in every government period. However, this work cannot be avoided from aspects of project failure or default. Projects that experienced default have occurred in Medan, Lhoksemawe, and Bukittinggi. This default occurred due to delays and inconsistencies in development which made the Medan city government request a refund of the total funds that had been given to the contractor or inconsistently because of the inaccuracy of payment for contractor services by the government. So, this article was written to find out the form of default by the Regional Government from the perspective of the MUI DSN - MUI fatwa no. 43 regarding this case. This research is qualitative research with the type of case study and normative law with data collection carried out using literature study and document study. The results of this research show that there are two forms of default committed by contractors, namely: (1) Delays in work (2) Delays in payment of funds, and (3) Non-compliance with plans and construction results. Perspective analysis of the MUI DSN – MUI fatwa no. 43 regarding this case the law is permissible. This shows the importance of fulfilling the contract in a joint agreement to achieve mutual success and comfort in making a contract or agreement.